2008
DOI: 10.1186/1751-0147-50-40
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and characterization of Treponema phagedenis-like spirochetes from digital dermatitis lesions in Swedish dairy cattle

Abstract: Background: Digital dermatitis in cattle is an emerging infectious disease. Ulcerative lesions are typically located on the plantar skin between the heel bulbs and adjacent to the coronet. Spirochetes of the genus Treponema are found in high numbers in the lesions and are likely to be involved in the pathogenesis. The aim of this study was to obtain pure cultures of spirochetes from cattle with digital dermatitis and to describe them further.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
35
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(39 citation statements)
references
References 20 publications
3
35
0
1
Order By: Relevance
“…One isolate each of T. pedis (TA4) (Pringle et al, 2009), T. parvum (B1119) and T. phagedenislike (V1) (Pringle et al, 2008) were cultured for 3-6 days to obtain a dense culture . Each culture was centrifuged to a pellet and material from the pellets was injected into small tissue samples of healthy porcine lung and fixated in formalin.…”
Section: Specificity Of Probesmentioning
confidence: 99%
“…One isolate each of T. pedis (TA4) (Pringle et al, 2009), T. parvum (B1119) and T. phagedenislike (V1) (Pringle et al, 2008) were cultured for 3-6 days to obtain a dense culture . Each culture was centrifuged to a pellet and material from the pellets was injected into small tissue samples of healthy porcine lung and fixated in formalin.…”
Section: Specificity Of Probesmentioning
confidence: 99%
“…These pathological characteristics resemble those of PDD in cattle [6,9]. Moreover, these spiral organisms detected in the canker lesions have not been identified, although the spirochetes detected in PDD have been identified as treponemal species [4,5,7,8,12,14,16,17].…”
mentioning
confidence: 97%
“…The authors [9] suggested that spirochetes may contribute to the pathology of equine chronic foot diseases, in a similar manner to the way in which spirochetes contribute to that of bovine papillomatous digital dermatitis (PDD) and contagious ovine digital dermatitis (CODD). Although the spirochetes detected in PDD and CODD have been identified as the genus Treponema [4,5,7,12,14,16,17], the phylogenetic relationship of the spirochetes detected in canker lesions remains unclear.To determine the spirochete phylogeny, we used 16S rRNA gene sequencing of randomly selected clones based on PCR with Treponema-specific primers to search for treponemes present in canker lesions in this study. Furthermore, we searched for the presence of treponemes in healthy hoof tissues.…”
mentioning
confidence: 99%
“…phagedenis-like spirochetes have been detected or isolated from PDD lesions in several countries including the USA and Europe [5,15,20], and Klitggard et al have suggested that this spirochete is one of the most prevalent treponemes in PDD lesions [9]. Therefore, we considered that data on the antimicrobial susceptibility of this organism would provide helpful information for the treatment of PDD and the development of a selective medium for isolation.…”
mentioning
confidence: 99%
“…To isolate treponemes from PDD lesions, RFP and ERFX are frequently used as selective agents at a concentration of 1~25 g/ml and 1~10 g/ml, respectively [5,15,18,20,21]. Leschine and Canale-Parola reported that addition of RFP to culture medium markedly increased the isolation rate of oral spirochetes [11].…”
mentioning
confidence: 99%